Herbie's game - Hallinan, Timothy (Hallinan, Timothy. Junior Bender mystery., 2014)
"It's everyday business when Wattles, the San Fernando Valley's top 'executive crook,' sets up a hit. He establishes a chain of criminals to pass along the instructions and the money, thereby ensuring that the hitter doesn't know who hired him. Then one day Wattles finds his office safe open and a single item missing: the piece of paper on which he has written the names of the crooks in the chain. When people associated with the chain begin to pop up dead, the only person Wattles can turn to solve his problem is Junior Bender, professional burglar and begrudging private eye for crooks"--